G555(P) Does the type of steroid used in the treatment of acute lymphoblastic leukaemia in childhood influence adult weight?. (May 2019) - Grey, HET; Davidson, A
Abstract : Aims: This study seeks to evaluate whether there is a difference in the body mass of UK survivors of childhood acute lymphoblastic leukaemia (ALL) between those who were treated with prednisolone (PRED) versus dexamethasone (DEX). It also aims to assess differences between the glucocorticoids in the relationship between the pattern of change in body weight during treatment and follow up. It is hoped that results will identify the potential for timely preventative measures. Methods: This study is a retrospective case note review of adult survivors of childhood ALL within a late effects service. Thirty adult survivors (≥18 years), treated with either PRED (n=18) or DEX (n=12), were selected. Height and weights recorded during treatment and long term follow up (LTFU) were used to calculate BMI (body mass index) during LTFU and compared between both glucocorticoids. Weight for age (WFA) Z-scores were calculated during treatment and correlated with LTFU BMI before comparing between the glucocorticoids. Results: The mean BMI of both groups was overweight at first adult LTFU (PRED BMI=27.3; DEX BMI=25.5) and most recent LTFU (PRED BMI=28.0; DEX BMI=25.9). There was no difference in overall BMI at any point or period during LTFU between PRED and DEX groups. The DEX group experienced a significantly smaller increase in BMI from end of treatment to first adult LTFU (SD=3.4, p<0.05) and most recent LTFU (SD=4.4, p<0.05). The PRED group showed significantly greater correlation between WFA Z-score at six months from treatment and first adult LTFU BMI. The DEX group showed significantly greater correlation in the total change of WFA Z-score during treatment with first adult LTFU BMI. Conclusions: Adult survivors of childhood ALL do not differ in LTFU BMI when treated with PRED or DEX. Those treated with the current standard glucocorticoid, DEX, experience smaller increases in BMI after treatment. Weight changes during treatment correlate differently with LTFU BMI depending on the type of GC. The results highlight potential warning signs during treatment which may enable early intervention to reduce the prevalence of high BMI in adulthood.